The Regulation of Personal Income Tax and Its Enforcement For Foreign Workers - Kurniawan Kurniawan; Maman Sudirman; Benny Djaja (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
Foreign workers who work in Indonesia are required to pay taxes, especially taxes on the salaries they receive. However, tax collectors are often considered to be detrimental to foreign workers, because they reduce the income from their salaries. The aim of this research is to analyze the regulations for imposing salary tax on foreign nationals who work in Indonesian territory and the sanctions that can be given to foreign nationals who do not pay tax from their salaries. The research method in this scientific journal uses a normative juridical approach using data available through Open Source. The results is based on the Tax Harmonization Law, which states that foreign citizens who have obtained work permits can automatically be said to be taxpayers. As for the imposition of PPH 21 income tax for salaries for foreign workers on fixed income, the amount of income subject to tax is in the Minister of Finance Regulation number 101/PMK.010/2016. The legal sanctions for foreign citizens do not pay their salary taxes include fines, interest sanctions and increased tax sanctions. The research contribution is to raise new scientific discipline for more comprehensive regulation of foreign taxpayers.